A feasibility study on TraceIT - Manglicmot, Leslie Dale; Reyes, Sophia Isabelle; Silang, Kim Patricia; Tan, Rizza Mariel (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
Educational software and improved assistive devices have been developing in the market with the growing acceptance of integrating technology in the curriculum. LearnIT, Inc. has opened new doors to discovering the development of reading and writing as initial phase to learning through the use of technology as instructional medium. TraceIT is a fun and educational software that allows users to recognize letters through tracing with the use of Kinect for Windows, mouse or track pad. The product earned its initial branding by garnering second place in the recent Imagine Cup Local Finals of Microsoft in 2012, currently contributing to the motion sensing device paradigm. TraceIT was initially developed for the use of the disabled children. Studies have shown that the use of motion sensing device has become beneficial in physical therapy and rehabilitation. Through careful analysis of the market demand, the software has proven to have a larger market that encompasses the disabled. The potential target market not only includes the disabled but young children who are learning how to read and write as well as language enthusiasts around the globe. The opportunities for TraceIT have been found to be in both non-mobile and mobile application development. However, based on the study, the mobile application market is saturated. Millions of apps are created every week with hopes of reaching a fair amount of downloaders to keep stable profit. Though risky, LearnIT, Inc., the developer of TraceIT, has more opportunities to explore the development of non-mobile application for motion sensing device. To keep up with the changing market and innovation in technology, LearnIT, Inc. has adopted an agile method of production that allows the developers to adapt to the needs of the market that is expected to change. Of the total Philippine target market of 199,740, an estimated 5.5% penetration (10,986) will occur on the first year which is expected to increase by 5% for the next five years. This target market is comprised of individuals with SEN that will benefit from TraceIT and class AB who have purchasing power. Total cost for the first year is estimated at PhP 4,137,204.43, inclusive of capital expenditure, operational expenses and others. It has been identified that there are four sources of funding - proprietors and developers, angel investors, venture capitalists and stock market. As a conservative estimate, the proprietors, developers and angel investors have been chosen as sources of funding where PHP 1. 7 million will be raised at Year Oto enable the venture to run for the next 5 years. The traditional financial analysis does not apply for TraceIT as the dynamics of the industry is unique where low liability is acceptable because of low capital investments. Though there is a decline in asset turnover projection, this translates to an increasing profit margin of 45% at year 5 which shows good protection against competitors trying to penetrate the market. Within one year, investors are assured of payback from their PHP 1.7 million investment. The venture shows positive net present value for both financial and socio-profitability which translates to good financial status and good return to the society.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Educational technology; Feasibility studies